(untitled) (Plant Tissue Culture and Biotechnology, 2011)
Nodal segments of Stemona tuberosa Lour. were found to proliferated without any differentiation on to MS supplemented with 3.0 mg/l BAP and 0.5 mg/l NAA under continuous dark condition. After 20 days of inoculation under dark condition the cultures were transferred to a daily cycle of 16/8 hrs light/dark photoperiod and there the proliferated nodal segments underwent direct organogenesis producing huge number of shoot buds (25.87/culture). The shoot buds underwent rapid elongation on a range of BAP (0.1 - 1.5 mg/l) and IBA (0.1 - 1.0 mg/l) supplemented MS. Rooting of elongated shoot buds was successfully achieved (90%) in half strength MS with 1.0 mg/l NAA. The plantlets were finally established in outside environment through a successive phase of acclima-tization. Key words: Nodal explant, Stemona tuberose, Rare medicinal plant, Direct organogenesis D. O. I. 10.3329/ptcb.v21i2.10238 Plant Tissue Cult. & Biotech. 21(2): 151-159, 2011 (December)